Análise da sustentabilidade ambiental nos aspectos de água e energia elétrica na Universidade Federal de São Paulo - Justi, Fernanda [UNIFESP] (2018)
Sustainability is a theme that generates many conflicts regarding its definition. Only recently after the appearance and the practice of environmental management it has been possible to perceive the associated influences from anthropic activities in the various levels in which man affects the planet. Universities are also set in this context, so that they are causing impacts and, at the same time, are generating knowledge in this topic. Therefore, the objective of this study is to evaluate environmental sustainability in the aspects of water and energy in Universidade Federal de São Paulo (UNIFESP). In order to do so, secondary data of water and electricity monthly consumptions from its campuses and Rectory were analyzed, from 2014 to 2016. Statistical analyzes were performed in the SPSS software, providing comparisons of the consumption that occurred between the years. It also generated comparisons of the pre- and post-intervention period that occurred in February 2015. The intervention was the publication of the Boas Práticas para Economia de Água e Energia by the Departamento de Gestão e Segurança Ambiental of UNIFESP (DGA-UNIFESP), and the publication of the Portaria MPOG nº 23/2015 containing measures to rationalize the consumption of water and energy. The results showed that the intervention caused a greater reduction in water consumption than in energy consumption, indicating that it is necessary to invest in more energy-efficient equipment, adopt more strict measures of awareness regarding the rational use of energy, use of natural light and evaluate the use of mechanisms to produce energy in loco. The practices that led to the reduction of water consumption should be maintained and improved.